Edupreneur Management: Transformation Program to Increase Entrepreneurial Interest Based on Malay Local Wisdom for Students of State Vocational School 2 Tanjungpinang: Manajemen Edupreneur: Program Transformasi Peningkatan Minat Wirausaha Berbasis Kearifan Lokal Melayu Bagi Siswa SMK Negeri 2 Tanjungpinang - Soehardi*, Dwi Vita Lestari; Almahfuz, Almahfuz; Putri, Chika Juliana (Universitas Lancang Kuning, 2024)
This community service aims to analyze the Malay local wisdom-based edupreneurship program at SMK Negeri 2 Tanjungpinang in an effort to improve students' entrepreneurial skills and interests. PAR method. Participatory Action Research (PAR) is a way to build bridges to connect people. PAR involves conducting research to define a problem or applying information into action as a solution to a defined problem. The results of the community service show that Malay local wisdom-based edupreneurship at SMK Negeri 2 Tanjungpinang has succeeded in fostering students' entrepreneurial spirit through the integration of Malay culture, which not only improves business skills but also strengthens their cultural identity. The obstacles faced include limited access to capital and technology, which are attempted to be solved through collaboration with external parties. In conclusion, this local wisdom-based edupreneurship program provides a positive contribution to the development of entrepreneurship and the preservation of local culture, especially at SMK Negeri 2 Tanjungpinang, and shows potential to be applied in other educational institutions.